Controlled anomalous transmission through plasma layers - Ivko, S.; Smolyakov, A.; Denysenko, I.; Azarenkov, N.A. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
We study propagation of a p-polarized electromagnetic wave through a two-layer plasma structure in an external magnetic field perpendicular to the incidence plane. It is shown that normally opaque plasma layer can be made absolutely transparent. The conditions for resonant transmission are obtained and analyzed. The influence of the external magnetic field on resonant transmission is studied. We show that one can control electromagnetic radiation transmitted through the plasma structure by altering the magnetic field. Изучается прохождение р-поляризованной электромагнитной волны через двухслойную плазменную структуру во внешнем магнитном поле, перпендикулярном плоскости падения. Показано, что непрозрачный плазменный слой может быть сделан абсолютно прозрачным. Условия резонансного прохождения получены и проанализированы. Изучено влияние магнитного поля на резонансное прохождение. Показано, что можно контролировать электромагнитное излучение, прошедшее через плазменную структуру, изменяя магнитное поле. Вивчається проходження р-поляризованої електромагнітної хвилі крізь двохшарову плазмову структуру в зовнішньому магнітному полі, перпендикулярному до площини падіння. Показано, що непрозорий плазмовий шар може бути зроблено абсолютно прозорим. Умови резонансного проходження отримано та проаналізовано. Вивчено вплив магнітного поля на резонансне проходження. Показано, що можна керувати проходженням електромагнітного випромінювання через плазмову структуру, змінюючи магнітне поле.